Carbon budgets and energy transition pathways. (14th July 2016) - van Vuuren, Detlef P; van Soest, Heleen; Riahi, Keywan; Clarke, Leon; Krey, Volker; Kriegler, Elmar; Rogelj, Joeri; Schaeffer, Michiel; Tavoni, Massimo
Abstract: Scenarios from integrated assessment models can provide insights into how carbon budgets relate to other policy-relevant indicators by including information on how fast and by how much emissions can be reduced. Such indicators include the peak year of global emissions, the decarbonisation rate and the deployment of low-carbon technology. Here, we show typical values for these indicators for different carbon budgets, using the recently compiled IPCC scenario database, and discuss how these vary as a function of non-CO2 forcing, energy use and policy delay. For carbon budgets of 2000 GtCO2 and less over the 2010–2100 period, supply of low carbon technologies needs to be scaled up massively from today's levels, unless energy use is relatively low. For the subgroup of scenarios with a budget below 1000 GtCO2 (consistent with >66% chance of limiting global warming to below 2 °C relative to preindustrial levels), the 2050 contribution of low-carbon technologies is generally around 50%–75%, compared to less than 20% today (range refers to the 10–90th interval of available data).